Prophylactic activity of caffeine in controlling Parkinson’s disease (Brazilian Journal of Health Research, 2024)
Introduction: In the world, it is estimated that Parkinson’s disease (PD) is the second most common degenerative neuropathology, being preceded only by Alzheimer’s disease. It is an idiopathic disease, which results from individual interactions with environmental factors, which lead to biochemical dysfunctions. It is known, however, that methylxanthines, like caffeine, have biological activities that are correlated with the pathophysiology of dementia. Objective: To verify the prophylactic activity of caffeine in controlling PD. Methods: A literature review was carried out by electronic search of scientific articles, published between 2015-2020, in the Scientific Electronic Library (SciELO), Latin American and Caribbean Center on Health Sciences Information (BIREME-PAHO-WHO), and the US National Library of Medicine (PubMed). The search was based on the search for the keywords “caffeine and Parkinson disease”. Results: Ten articles were selected, of which five suggested that caffeine has therapeutic potential in the treatment of PD in an animal model; two indicated that, in vitro, caffeine has therapeutic potential; three did not correlate caffeine with clinical improvement in PD, in cases of already established disease in humans; two indicated that caffeine consumption as a protective factor for the development of PD. Conclusion: Caffeine has antiparkinsonian activity in vitro and in vivo. However, this effect is not reproduced in clinical trials, which indicates translational ineffectiveness. However, there is still a need for larger multicentric clinical studies, with caffeine alone, aimed at investigating its usefulness, or not, as an adjuvant therapy in the treatment of PD.
Keywords: Parkinson’s disease; Caffeine; Control